Fabrication of novel resinous diamond composites with acrylonitrile butadiene styrene/polyvinyl chloride/dioctyl phthalate/diamond by hot pressing molding. Issue 10 (12th March 2019) - Chen, Fengjun; Liang, Huochang; Yin, Shaohui; Huang, Shuai; Tang, Qingchun
Abstract: Abstract : Uniform distribution of diamond grains is difficult to achieve using traditional fabrication of the micro grinding wheel. The design and performance of novel resinous diamond composites (RDCs) fabricated by hot pressing molding were studied to fabricate micro resinous diamond grinding wheels. The physical and mechanical properties of RDCs were analyzed by constructing and simulating five kinds of RDCs, including acrylonitrile butadiene styrene (ABS)/polyvinyl chloride (PVC)/dioctyl phthalate (DOP)/diamond materials with different mass ratios. Diamond grains presented good compatibility with the ABS–PVC–DOP copolymer, which resulted in improved mechanical properties of RDCs. RDC1–RDC5 samples were fabricated, and their hardness, surface roughness, and infrared spectra were analyzed. The optimal mass ratio of ABS/PVC/diamond/DOP for fabricating RDCs was 62.5/18.6/10.6/8.3. The results provide guidance in fabricating novel materials for resinous diamond grinding wheels with desirable performances for precision and ultraprecision machining.